Assessing academic impairment in college students with disabilities: A new measure to promote evidence-based accommodation granting - Weis, Robert; Waters, Evelyn A.; Hassler, Michaela (Frontiers in Education, 2022)
College students with disabilities may be entitled to academic accommodations such as additional time on exams, testing in a separate setting, or assistance with note-taking. To receive accommodations, students must request services from their college and show that they experience substantial limitations in academic functioning. Without norm-referenced data, it is difficult for college disability support professionals to determine if students’ self-reported academic problems reflect substantial limitations characteristic of a disability, or academic challenges experienced by most other students. The Academic Impairment Measure (AIM) is a brief, multidimensional, norm-referenced rating scale that can help professionals identify college students with significant impairment who need academic support. Exploratory and confirmatory factor analysis indicate that the AIM assesses seven distinct and interpretable domains of academic functioning relevant to postsecondary students. Initial studies also provide evidence of internal and temporal consistency; composite reliability; content, convergent and discriminant validity; and the ability to differentiate students with and without disabilities. Finally, the AIM includes a response validity scale to detect non-credible ratings. Normative data from a large, diverse standardization sample allow professionals to use AIM scores to screen students for significant impairment, tailor accommodations to students’ specific limitations, and monitor the effectiveness of accommodations over time.